2018
DOI: 10.1038/s41598-018-31997-z
|View full text |Cite
|
Sign up to set email alerts
|

X-ray structure of full-length human RuvB-Like 2 – mechanistic insights into coupling between ATP binding and mechanical action

Abstract: RuvB-Like transcription factors function in cell cycle regulation, development and human disease, such as cancer and heart hyperplasia. The mechanisms that regulate adenosine triphosphate (ATP)-dependent activity, oligomerization and post-translational modifications in this family of enzymes are yet unknown. We present the first crystallographic structure of full-length human RuvBL2 which provides novel insights into its mechanistic action and biology. The ring-shaped hexameric RuvBL2 structure presented here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…Calculation of the radii of gyration resulted in values of 47.7 Å for apo RUVBL2, 47.9 Å for RUVBL2 + DMSO and 47.2 Å for RUVBL2 + Sorafenib. These values agree with previously observed dimensions for human RUVBL2 by X-ray crystallography (52 Å) [14]. To further investigate differences in the overall fold and flexibility of RUVBL2, dimensionless Kratky analysis was performed.…”
Section: Sorafenib Does Not Affect the Oligomerization Of Ruvbl2 Nor supporting
confidence: 87%
See 2 more Smart Citations
“…Calculation of the radii of gyration resulted in values of 47.7 Å for apo RUVBL2, 47.9 Å for RUVBL2 + DMSO and 47.2 Å for RUVBL2 + Sorafenib. These values agree with previously observed dimensions for human RUVBL2 by X-ray crystallography (52 Å) [14]. To further investigate differences in the overall fold and flexibility of RUVBL2, dimensionless Kratky analysis was performed.…”
Section: Sorafenib Does Not Affect the Oligomerization Of Ruvbl2 Nor supporting
confidence: 87%
“…Further experiments performed on RUVBL2∆DII confirmed that the ATPase activity of RUVBL2 with truncation of its insertion domain was not inhibited by sorafenib; therefore, leading us to propose that the mechanism of action of sorafenib is mediated through its interaction with DII or that DII flexibility causes RUVBL2 to populate certain conformations to which sorafenib can bind. Recently, it was proposed that the RUVBL2 N-terminal segment may function as a lid for the nucleotide-binding site and the binding of ATP could induce the recruitment of DII by the N-terminal segment [14,16]. In this sense, binding of sorafenib to DII would influence the dynamics of DII, consequently affecting RUVBL2 nucleotide exchange rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of RUVBL1-RUVBL2 ATPase activity is poorly understood. The Ntermini of RUVBL1 and RUVBL2 contain two histidine residues, His 25 and His 27 in RUVBL2, that bind the nucleotide and contribute to maintain it within its binding pocket (Munoz-Hernandez et al, 2019;Silva et al, 2018). Here, cryo-EM reveals that the NMD factor DHX34 directly affects the conformation of RUVBL2 N-termini and decreases ATP hydrolysis.…”
Section: Discussionmentioning
confidence: 94%
“…We first analyzed the structure of the RUVBL1-RUVBL2 ring using a mask that removed the influence of DHX34 and the protruding OB-fold domains during image processing ( The most striking feature in the cryo-EM map is that the N-terminal regions that contribute to nucleotide binding (Munoz-Hernandez et al, 2019;Silva et al, 2018) are visualized in RUVBL1 but not in any of the three RUVBL2 subunits ( Figure 3A, B). We performed several experiments to fully verify that every RUVBL2 in the complex lacked density for the N-terminal region.…”
Section: Dhx34 Induces Conformational Changes In the N-termini Of Ruvbl2mentioning
confidence: 99%